Review of area exclosure practices for sustainable land management and erosion control in Ethiopia: objectives and PRISMA review - Teku, Degfie; Mengesha, Yeshifana Alemneh; Kesete, Nega (Frontiers in Conservation Science, 2025)
IntroductionEthiopia is grappling with a severe soil erosion crisis, losing an estimated 1.5 billion tons of soil annually due to unsustainable agricultural practices exacerbated by climate change. This widespread land degradation poses serious threats to agricultural productivity, ecological stability, and the socio-economic well-being of rural communities. In response, area exclosures lands designated for natural regeneration have gained prominence as a vital strategy for sustainable land management (SLM). They offer substantial potential to control soil erosion, restore degraded ecosystems, and enhance biodiversity conservation. This systematic review critically evaluates the effectiveness of area exclosures in Ethiopia, focusing on their environmental impacts, socio-economic outcomes, and the role of community participation in their success.MethodologyFollowing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, this review systematically analyzed peer-reviewed literature, reports, and policy documents on area exclosure practices across Ethiopia’s diverse ecological and socio-economic contexts. Rigorous inclusion and exclusion criteria were applied to ensure relevance and quality. The search covered multiple academic databases and grey literature sources. A thematic analysis synthesized findings related to environmental benefits, socio-economic impacts, institutional challenges, and policy implications.ResultsThe review reveals that area exclosures significantly reduce soil erosion, with some cases reporting up to 75% reductions in soil loss. Positive ecological outcomes include improved soil fertility, increased vegetation cover, enhanced species richness, and better water retention and infiltration. Socio-economically, area exclosures support alternative livelihoods, promote carbon sequestration, and contribute to ecosystem resilience. However, challenges persist, notably insecure land tenure, limited financial resources, inadequate policy enforcement, and weak technical capacity. Community participation emerged as a critical factor for effective implementation, long-term sustainability, and local ownership.Discussion and recommendationsWhile area exclosures demonstrate significant potential as a nature-based solution to Ethiopia’s land degradation challenges, scaling up their impact requires addressing persistent socio-economic and institutional barriers. Strengthening land tenure security, enhancing community engagement, and establishing sustainable financing mechanisms are crucial. Furthermore, policy coherence and institutional capacity-building should be prioritized to ensure long-term success. The study recommends future research focus on long-term ecological monitoring and socio-economic assessments to guide adaptive management and inform evidence-based policy interventions supporting Ethiopia’s resilience against land degradation and climate change.